An introduction to ecological economics - Costanza, Robert (St. Lucie Press, 1997)
Ecological economics is a way of rethinking the relationship between humans and the environment and working out the implications of how we manage our lives and the planet. An Introduction to Ecological Economics offers a starting point for undergraduate and graduate students and environmental professionals interested in this transdisciplinary field. Beginning in Section 1 with a description of some current problems in society and their underlying causes, Section 2 then takes a historical perspective to explain how world views regarding economics and ecology have evolved. Section 3 presents the fundamental principles of ecological economics, and Part 4 outlines and discusses a set of policies for creating a sustainable society as well as instruments that could be used to implement those policies. A conclusions section summarizes the main points of the book and proposes prospects for the future. Let An Introduction to Ecological Economics introduce you to important issues affecting our ecology, our economy, our world.